A four frame analysis of factors impacting the uptake of the scholarship of teaching ad learning in a college of education - Mbati, L. (South African Journal of Higher Education, 2025)
The Scholarship of Teaching and Learning (SoTL) lies at the intersection of various disciplines and involves post-secondary practitioners conducting inquiries into teaching and student learning for the purpose of improving teaching and learning. While the SoTL is present in the South African higher education institution’s strategic goals, there exists a challenge in the uptake of the SoTL by academics. Literature reveals several tensions between academic disciplines and the SoTL identities, namely workload and time, disciplinary-based and methodological-based disparities, the relative “value” of SoTL in relation to disciplinary research, lack of knowledge around what the SoTL is, and/or what it entails, which all serve as some of the challenges facing the growth of the SoTL. In an attempt to place the practice of, and challenges to the SoTL in context, this phenomenology sought to explore the impediments to the SoTL at a South African higher education institution through the lens of the Four Frame Analysis (Bolman and Deal 2008). The frame serves as an agent to disrupt conventional wisdom prevalent within institutional cultures, to shift thinking and to enable leaders to uncover the levers and barriers of the SoTL. Findings indicate the importance of aligning and resourcing of the SoTL strategic goals. Recommendations include professional development in the area of the SoTL and the review of funding and rewards strategies that impede the multi- and inter-disciplinary SoTL.